Sentencing guidelines under the social disability model (Revista de Investigaciones Universidad del Quindío, 2021)
This article describes the social model of disability, its antecedents and scope in the legal system. Its objective is to provide guidelines for the legal operator to identify whether it is necessary to make reasonable adjustments when passing judgment in the judicial procedure, defining and exemplifying each of these.
Keywords: Reasonable accommodation; social model of disability; people with functional diversity; easy-to-read sentence